Struktur Komunitas dan Preferensi Habitat Ikan Karang pada Terumbu Buatan di Teluk Awang dan Teluk Bumbang, Pulau Lombok - Ria Faizah; Lilis Sadiyah; Aisyah, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Community Structure and Habitat of Coral Fish on Artificial Reef in Awang and Bumbang Bay, Lombok Island. Artificial reefs which were placed in Teluk Awang and Teluk Bumbang intended to restore habitat fish resources. This paper aims to evaluate the development of artificial reefs in both locations. The activities was conducted in June and December 2015. Data collection included fish and benthic communities, biological parameters (phytoplankton, zooplankton, meroplanton), physical parameters (temperature, salinity, conductivity, pH, turbidity, dissolved oxygen), and chemical parameters waters (nitrates and phosphates). Observation of fish community using SCUBA diving equipment, underwater sheets, stationery and GPS, then visual observations using a modified stationary visual census technique. Visual recorded also used for benthic communities. Water sampling taken on the surface and bottom at depths of 9 m and 11 m using water quality checker. Biological parameters were taken using 60 µ, 300 µ and plankton net sizes 700 µ. Nutrients were observed in the laboratory by taking water samples in situ. Laboratory tests were carried out for nutrients as well as plankton and meroplankton. Benthic communities were categorized into four life forms, namely live coral covered, dead coral, biota (algae and other biota) as well as the abiotic component. Habitat preferences identified through analysis of factors related to fish abundance by principal component analysis method. The results showed that on those artificial reefs in Awang and Bumbang Bay found as many as 8 - 16 species of coral fish belongs to 15 families, dominated by Apogonidae (Archamia fucata), Pomacentridae (Neopomacentrus cyanomos) and Phempherididae (Phempheris oulensis), ranges of the abundance 268 to1088 individual. The ecological index showed low to moderate type of diversity, the dominance index does not indicate the dominance of certain species and the evenness index indicated that the fish dispersal characteristic is quite flat. Fish habitat preference in Awang Bay supported by the presence of algae and other biota, nutrients, and salinity. While in Teluk Bumbang supported by the abundance of fito-zooplankton, dissolved oxygen, and turbidity